Post-surgical analgesic properties and pharmacokinetics of tramadol in dogs undergoing elective surgery - Buhari, Salisu (2012)
Post-surgical pain is a distressing phenomenon associated with potential tissue damage in dogs. Many pain relief options such as non-steroidal anti-inflammatory drugs (NSAIDs) and opioid receptor agonists range widely in both their therapeutic and side effects. Atypical opioids such as tramadol are used in veterinary practice as an alternative due to their dual mechanism of action and have been designed to overcome the side effects through an opiate-sparing effect. Despite the wide clinical applications of tramadol in dogs, its analgesic efficacy following subcutaneous administration, renal and hepatic safety following repeated administration during surgery and the effect of surgery as well as gender on its pharmacokinetics, are not well documented. Thus, this study was conducted to compare the effect of routes of administration of tramadol on post-surgical pain management in dogs, the effects of single and second dose of tramadol administration on renal and hepatic changes in dogs undergoing surgery and the effects of surgery on the pharmacokinetics of tramadol following subcutaneous and intravenous administration in male and female dogs. It was therefore hypothesized that subcutaneous administration of tramadol can provide equivalent analgesia when given intravenously route of administration, and that first and second dose of tramadol can provide post-surgical analgesia without pathological effects. Also, surgery and gender differences can influence the pharmacokinetic parameters of tramadol in dogs. A ‗double-blind‘ trial was carried out comparing the analgesic efficacies of tramadol (3 mg/kg) given subcutaneously (SC) with intravenous (IV) administration following ovariohysterectomy. Eighteen female dogs were divided into 3 groups of six in each group. Tramadol (3 mg/kg) was given to Group 1 subcutaneously and to Group 2 intravenously, Group 3 was a negative control (without tramadol). A significant increase in pain perception was observed in group 3, while groups 1 and 2 had an equal postoperative analgesic activity indicated by the analgesiometer test, serum interleukin 6(IL-6) and serum beta-endorphins (β-end) physiological parameters. The measurement of serum interleukin 6 (IL-6) and serum beta-endorphins (β-end) correlated with post-surgical pain stimulation in all groups. A higher relationship was observed between analgesiometer values and β-end. Twenty-five female dogs, five in each group, were used to study the effect of single and double doses of tramadol on hepatic and renal changes and functions. Groups 1 and 2 received 3 mg/kg of tramadol by subcutaneous and intravenous injections, respectively, during premedication. Groups 3 and 4 received similar doses of tramadol during premedication, which was repeated 2 hours after the initial dose through subcutaneous and intravenous injections, respectively. Group 5 served as a negative control. Blood samples (2 mL) were taken at 0, 2 and 4 hr after tramadol administration while liver and kidney biopsies were taken before the end of surgery 5 hours after first tramadol administration. Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels were significantly lower in groups 2, 3 and 4 when compared to group 5 at 4 hours post-tramadol administration. Significant increases in AST were observed in groups 1, 3 and 5 at 2 hours and at 4 hours in groups 1 and 5. Histopathological changes in the liver and kidney included congestion, edema and cellular infiltration which occurred less frequently in groups 3 and 4. The changes suggested side effects of pentobartone anaesthesia and not tramadol. Thirty-six dogs comprising twenty-four females and twelve males were used in studying the influence of surgery and gender-differences on tramadol pharmacokinetics. The dogs were grouped into six equal groups of six dogs each viz: groups 1 and 2 were female dogs and received 3 mg/kg tramadol via the intravenous and subcutaneous route, respectively, and both underwent surgery; groups 3 and 4 were also female dogs and received similar doses of tramadol via the intravenous and subcutaneous route, respectively, without surgery, while groups 5 and 6 were male dogs without surgery and were given tramadol via the intravenous and subcutaneous route, respectively. The outcome of this study showed that surgery significantly affected the biotransformation process of tramadol, as indicated by a 2-fold increase in its elimination half-life (1.10 ± 0.18 hr) in groups 1 and 2 compared to groups 3 and 4 (0.49 ± 0.07 hr). Serum tramadol concentration was significantly higher in groups 1 and 2 (770.21 ± 117.76 ng/ml) compared to groups 3 and 4 (117.61 ± 85.16 ng/ml) which was reflected by a significantly lower clearance value (3.98 ± 0.56 ml/min/kg) in groups 1 and 2 compared with groups 3 and 4 (21.06 ± 9.34 ml/kg). The results suggested that surgery and anaesthesia have an effect on both the distribution and elimination of tramadol in dogs. A significantly shorter duration to reach high plasma tramadol concentration (0.17±0.01 hr) in male dogs compared with (0.75±0.01 hr) female dogs was observed. The rate of movement of the tramadol from the first compartment to the second compartment was significantly (p < 0.05) slower (5.99±4.1 l/hr) in males, compared with 13.34±12.58 l/hr found in female dogs. Similarly, higher (p < 0.05) systemic bioavailability (29.65±11.7%) among males was observed compared to females (15.68±4.14%), suggesting a faster passage of the drug from blood to the organs in female dogs. There was no significant difference in the plasma concentration, distribution half life, elimination half life and clearance was observed between intravenous and subcutaneous routes of tramadol administration. This study concluded that: the subcutaneous route of administration of tramadol was similar to the intravenous route in the management of post-surgical pain in dogs. Also, an additional dose of tramadol at 3 mg/kg administered intravenously or subcutaneously is safe at 2 hours interval during surgery without causing hepatic and renal damage in dogs. Finally, after subcutaneous administration of tramadol in dogs, the drug was rapidly absorbed into the blood stream while the bioavailability was very low due to surgery and anaesthesia. These findings suggested that in the dog, the subcutaneous pharmacokinetics of tramadol is similar to the intravenous and both routes are influenced by surgery and anaesthesia. In addition, male dogs require a higher frequency of tramadol administration due to a faster biotransformation,hence the concentration profile supports an effective surgical and clinical duration of three hours in female dogs.